2008
DOI: 10.1111/j.1740-0929.2007.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the bioactive components of the ecotypes and cultivars of plantain (Plantago lanceolata L.) herbs

Abstract: The concentrations of the bioactive components, acteoside, aucubin and catalpol, and the production yield, crude protein (CP) and crude ash contents in 25 ecotypes (Et) of plantain (PL, Plantago lanceolata L.), found in northern Japan, and commercial cultivars, Grasslands Lancelot (GL) and Ceres Tonic (CT), were investigated. The quantitative determination of bioactive components was performed by high performance liquid chromatography. The acteoside content of some of the 25 Et was significantly higher (P < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
1
11
1
Order By: Relevance
“…Analysis of proximate components of the experimental diets were performed according to AOAC 10 as described before 11 and the total polyphenol contents of hop was determined according to Folin-Denis method 12 as described in our previous paper 13. The NH 3 -nitrogen (N) content of the rumen fluid was determined using colorimetric method 14.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of proximate components of the experimental diets were performed according to AOAC 10 as described before 11 and the total polyphenol contents of hop was determined according to Folin-Denis method 12 as described in our previous paper 13. The NH 3 -nitrogen (N) content of the rumen fluid was determined using colorimetric method 14.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Cowan et al (2012) found positive response of addition of GLP-1 receptor agonist with Table 4 Effects of plantain (Plantago lanceolata L.) and heat exposure (30°C) on plasma glucose production (PGP) and utilization (PGU) rates and response of plasma glucose utilization (RPGU) to exogenous insulin infusion in sheep insulin in reducing insulin doses, further weight loss and risk of hypoglycemia in individuals having insulin resistance. Catalpol is one of the bioactive components of plantain (Al-Mamun et al, 2008a), which might be responsible for the insulin resistance. Because, the catalpol was found has the equal potentiality to work as like as GLP-1 receptor agonist (Jia et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was performed using a crossover design with two 23-day periods in which either PL-or MH-diets were fed (Figure 1). Fresh plantain grown in the experimental field of Iwate University was cut and delivered daily (for details about the location and cultivation please see Al-Mamun et al, 2008a). The mixed hay and fresh plantain was chopped and fed to the animals in order to avoid choice feeding, as the morphology, such as leaves size, stems physical properties, can stimulate foraging behavior of sheep (Provenza, 2003;Smit et al, 2005;Barre et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide array of environmental factors have been shown to influence the types or concentrations of specialized metabolites produced by the model Plantago species, including plant/leaf age and phenology (Barton, 2008;Hanley et al, 2013;Pankoke et al, 2013;Sutter & Muller, 2011), herbivore and pest damage (Bowers, Collinge, Gamble, & Schmitt, 1992;Sutter & Muller, 2011), genotype (Adler, Schmitt, & Bowers, 1995;Al-Mamun, Abe, Kofujita, Tamura, & Sano, 2008;Barton, 2007;Marak, Biere, & van Damme, 2002;Zubair et al, 2012), habitat type (Adler et al, 1995), plant competition (Barton & Bowers, 2006;Pankoke, Hopfner, Matuszak, Beyschlag, & Muller, 2015;Waschke, Hancock, Hilker, Obermaier, & Meiners, 2015), associations with microorganisms including arbuscular mycorrhizal fungi (Bennett & Bever, 2007;Bennett, Macrae, Moore, Caul, & Johnson, 2013;Fontana, Reichelt, Hempel, Gershenzon, & Unsicker, 2009;Schweiger et al, 2014;Wang, Bezemer, van der Putten, & Biere, 2015), nutrient levels (Darrow & Bowers, 1999;Jarzomski, Stamp, & Bowers, 2000;Miehe-Steier, Roscher, Reichelt, Gershenzon, & Unsicker, 2015;Pankoke et al, 2015), UV levels (McCloud & Berenbaum, 1999;Murai et al, 2009), and variation in geography and climate (Mølgaard, 1986;Murai et al, 2009;Pellissier, Roger, Bilat, & Rasmann, 2014;Reudler & Elzinga, 2015).…”
Section: Introductionmentioning
confidence: 99%